Emodin Reverses the Epithelial–Mesenchymal Transition of Human Endometrial Stromal Cells by Inhibiting ILK/GSK-3β Pathway - Zheng Q; Wang J; Li W; Chen X; Chen S; Chen L (Dove Medical Press, 2020)
Qiaomei Zheng, Jinhua Wang, Wenwen Li, Xiaoyun Chen, Shaozhan Chen, Lihong Chen Department of Obstetrics and Gynecology, The First Affiliated Hospital of Fujian Medical University, Fujian Medical University, Fuzhou, Fujian 350001, People’s Republic of ChinaCorrespondence: Lihong ChenDepartment of Obstetrics and Gynecology, The First Affiliated Hospital of Fujian Medical University, Fujian Medical University, 20 Chazhong Road, Fuzhou, Fujian 350001, People’s Republic of ChinaTel +86-059187982061Fax +86-059187981028Email chenlihong_0102@126.comPurpose: To explore the exact mechanism through which emodin down-regulates the migration and invasion abilities of endometrial stromal cells. Moreover, to explore the theoretical basis of emodin in the treatment of endometriosis.Patients and Methods: Endometriosis endometrial stromal cells (EESs) were cultured from 15 women with endometriosis and control endometrial stromal cells (CESs) were cultured from 12 women without endometriosis. The levels of proteins were evaluated by Western blot. The migration and invasion abilities of cells were detected by transwell assays.Results: The abilities of migration and invasion of EESs were much stronger than those of CESs. After treated with emodin, the migration and invasion abilities of EESs and CESs were significantly down-regulated, and the levels of integrin-linked kinase (ILK) and p-GSK-3β were statistically down-regulated in EESs. Besides that, the expression of keratin was up-regulated while the expression of vimentin, β-catenin and slug were all down-regulated by emodin in a dose- and time-dependent manner. Silencing of ILK gene in EESs also achieved the above effects, which were strengthened by emodin. Conversely, exogenous expression of ILK in CESs increased the expression of p-GSK-3β, which were abrogated by emodin. Furthermore, SB216763 increased migration and invasion abilities of CESs by facilitating the epithelial–mesenchymal transition (EMT) through up-regulating levels of p-GSK-3β, β-catenin and slug, which were also abrogated by emodin.Conclusion: Emodin inhibits the migration and invasion abilities of human endometrial stromal cells by reversing the EMT via ILK/GSK-3β pathway. So, emodin may be considered as a promising targeted therapy for endometriosis.Keywords: emodin, endometriosis, EMT, ILK, GSK-3β